2000
DOI: 10.1038/modpathol.3880018
|View full text |Cite
|
Sign up to set email alerts
|

Value of the Mesothelium-Associated Antibodies Thrombomodulin, Cytokeratin 5/6, Calretinin, and CD44H in Distinguishing Epithelioid Pleural Mesothelioma from Adenocarcinoma Metastatic to the Pleura

Abstract: Until recently, the standard approach of most laboratories in distinguishing epithelioid pleural mesothelioma from metastatic adenocarcinoma has been a negative result from a panel of adenocarcinoma-associated antibodies. However, several "mesothelium-associated" antibodies have been proposed as useful in this situation, and we have applied four of these putative mesothelioma markers-thrombomodulin, cytokeratin 5/6, calretinin, and CD44H-to a series of 61 epithelioid pleural mesotheliomas and 63 metastatic ade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
152
1
7

Year Published

2000
2000
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(168 citation statements)
references
References 29 publications
8
152
1
7
Order By: Relevance
“…19,22 Previous studies suggested that D2-40 and CK 5/6 are specific to mesothelium and recommended their use to differentiate mesothelioma from serous carcinoma of the ovary. 13,23,24 In our study, D2-40 and CK 5/6 expression was demonstrated in a substantial number of serous carcinoma of ovarian (23.2 and 55.4%, respectively) and endometrial origin (43.2 and 37.8%, respectively). Nevertheless, unlike the diffuse reactivity characteristic to mesothelioma, the expression of D2-40 and/or CK 5/6 in serous carcinomas was usually confined to a subset of the neoplastic cells; typically the stain was positive in less than 25% of the cells.…”
Section: Discussionsupporting
confidence: 56%
“…19,22 Previous studies suggested that D2-40 and CK 5/6 are specific to mesothelium and recommended their use to differentiate mesothelioma from serous carcinoma of the ovary. 13,23,24 In our study, D2-40 and CK 5/6 expression was demonstrated in a substantial number of serous carcinoma of ovarian (23.2 and 55.4%, respectively) and endometrial origin (43.2 and 37.8%, respectively). Nevertheless, unlike the diffuse reactivity characteristic to mesothelioma, the expression of D2-40 and/or CK 5/6 in serous carcinomas was usually confined to a subset of the neoplastic cells; typically the stain was positive in less than 25% of the cells.…”
Section: Discussionsupporting
confidence: 56%
“…16,17 In 1996, Doglioni et al 16 reported strong calretinin expression in all 36 epithelioid mesotheliomas, but only focal staining was found in 28 (10%) of 294 adenocarcinomas of various origins and in 10 (18%) of 55 squamous carcinomas also of various origins. While many subsequent investigations have confirmed the usefulness of calretinin immunostaining in the differential diagnosis between mesotheliomas and lung adenocarcinomas, 8,[18][19][20][21][22][23][24][25][26][27][28][29] only a relatively few studies have been published on the expression of this marker in squamous carcinomas of the lung. 3,6,26,30 In the present investigation, all of the mesotheliomas exhibited diffuse strong positivity for calretinin, thus confirming the findings of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Calretinin is expressed in both the cytoplasm and nucleus. According to the literature, its expression in malignant mesothelioma varies, [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] but most authors report frequent expression in epithelioid malignant mesothelioma, with only few studies reporting expression below 90%. Interestingly, calretinin expression has been described in a wide variety of cells, including steroid-producing cells of the testis and ovary, adipocytes, eccrine-glands, keratinizing thymic epithelial cells and numerous tumors, for example Merkel cell carcinoma, Leydig cell tumors of the testis, esthesioneuroblastoma, adenomas of the adrenal gland, small cell carcinoma of the lung and adenomatoid tumor.…”
mentioning
confidence: 99%